Current status, challenges and analysis of financial investment for students: A case study of Vietnam (International Journal of Scientific Research and Management (IJSRM), 2024)
In the dynamic landscape of global finance, the necessity for financial literacy has become increasingly prominent, especially among younger generations who face unprecedented financial risks and complexities. The paper outlines the critical role of financial education within school curricula, emphasizing its importance in preparing youth to navigate the complexities of financial products and services effectively. As financial responsibilities and decision-making increasingly shift from institutions to individuals, the need for comprehensive financial education from an early age is more pronounced than ever. The paper explores various aspects of implementing financial education in schools, addressing the challenges of integrating such programs into existing curricula, securing necessary resources, and adequately training educators. Through a review of successful case studies from different countries, such as Australia, Brazil, and the United States, effective strategies and practices are highlighted. Particularly, we focus on the analysis the financial case studies of Vietnamese students. These examples demonstrate the importance of political support, stakeholder involvement, and sustainable program implementation to ensure the longevity and impact of financial education initiatives. Additionally, the paper provides a comparative analysis of financial education learning frameworks, which illustrates the diverse approaches tailored to specific educational and national contexts. This analysis underscores the importance of adapting financial education to meet local needs while aligning with broader educational goals. Furthermore, some key policy recommendations are offered to guide schools in supporting and committing to financial education. These include developing clear, measurable objectives for financial literacy programs, creating high-quality teaching materials, and fostering collaborations among governments, educational institutions, and financial experts. Lastly, the paper discusses methods for monitoring and evaluating the effectiveness of financial education programs. It stresses the need for both quantitative and qualitative assessments to ensure these initiatives meet their goals and contribute to the overall financial well-being of students. The conclusion calls for a sustained commitment to financial education, advocating for its integration into national educational policies and curricula. This strategic approach aims to leverage significant economic events to reinforce the value of financial literacy, ensuring that future generations are equipped to make informed financial decisions and contribute positively to the economy.